The non-alkaloidal constituents of Cephalotaxus mannii, collected in Lam Dong province - Lieu, Nguyen Thi; Loc, Tran Van; Phuong Thao, Tran Thi; Luu, Nguyen Thi; Anh, Ho Ngoc; Thu Ha, Le Thi; Chien, Tran Van; Ninh, Pham Thi; Phong, Dinh Thi; Sung, Tran Van (Vietnam Journal of Chemistry, 2016)
Three non-alkaloidal constituents: harringtonolide (nor-diterpene lactone), epicatechin and epigallocatechin have been isolated from Cephalotaxus mannii, collected in Lam Dong province, Vietnam in the frame work of the Tay Nguyen program III (TN III-15). Their structures were elucidated by the spectroscopic methods as the IR, ESI-MS, HR ESI-MS and NMR (1D, 2D) spectroscopy and comparison with published data. This is the first report of these compounds from Cephalotaxus mannii. Keywords. Cephalotaxus mannii, harringtonolide, epicatechin, epigallocatechin.